2013
DOI: 10.4067/s0716-97602013000300001
|View full text |Cite
|
Sign up to set email alerts
|

Breeding in peach, cherry and plum: from a tissue culture, genetic, transcriptomic and genomic perspective

Abstract: This review is an overview of traditional and modern breeding methodologies being used to develop new Prunus cultivars (stone fruits) with major emphasis on peach, sweet cherry and Japanese plum. To this end, common breeding tools used to produce seedlings, including in vitro culture tools, are discussed. Additionally, the mechanisms of inheritance of many important agronomical traits are described. Recent advances in stone fruit transcriptomics and genomic resources are providing an understanding of the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 110 publications
2
29
0
1
Order By: Relevance
“…The recent release of the complete peach genome sequence (Verde et al, 2013) together with four almond genome sequences (Koepke et al, 2013) and the sweet cherry genome publicly available since 2013 (Carrasco et al, 2013), offer new possibilities for integrating genetic and genomic approaches to find new CGs for flowering time in perennial plants (Martínez-Gómez et al, 2012). …”
Section: Genomic Studiesmentioning
confidence: 99%
“…The recent release of the complete peach genome sequence (Verde et al, 2013) together with four almond genome sequences (Koepke et al, 2013) and the sweet cherry genome publicly available since 2013 (Carrasco et al, 2013), offer new possibilities for integrating genetic and genomic approaches to find new CGs for flowering time in perennial plants (Martínez-Gómez et al, 2012). …”
Section: Genomic Studiesmentioning
confidence: 99%
“…Due to the high degree of heterozygosity of plum and its home hexaploid nature, it is difficult to investigate the inheritance of signs [9,[15][16][17]. The plum fruit size is inherited as a quantitative trait [7,15,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Matveyev (1987), studying the size of fruits in hybrid seedlings of domestic plums, found that the coefficient of heritability of this trait in a broad sense (H2) is 0.11. In plums, the coefficient of heritability of the fruits size in the narrow sense is 0.50 -0.52 [22,23]. This means that the correct selection of parents by phenotypic values of hybridization will lead to significant progress in the breeding of plums to increase the size of the fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite an estimated genome size of 225–330 Mb [8], [9], sweet cherry is lacking in genomic information in comparison with other prominent Rosaceae members, including peach and apple [10], [11]. Linkage maps and molecular markers have been developed for sweet cherry [12] as well as peach and almond, two other members of the sub-family Prunoideae [13], [14], [15], and a comprehensive and advanced draft of the peach genome serves as the foundation for several comparative studies [10].…”
Section: Introductionmentioning
confidence: 99%